Antimicrobial Photodynamic Therapy: Photodynamic Antimicrobial Effects of Malachite Green on Staphylococcus, Enterobacteriaceae, and Candida - Junqueira, Juliana Campos [UNESP]; Ribeiro, M. A. [UNESP]; Rossoni, R. D. [UNESP]; Barbosa, J. O. [UNESP]; Querido, S. M. R.; Jorge, A. O. C. [UNESP] (Mary Ann Liebert, Inc., 2010)
Objective: This study investigated in vitro the photodynamic antimicrobial effects of the photosensitizer malachite green on clinical strains of Staphylococcus, Enterobacteriaceae, and Candida. Materials and Methods: Thirty-six microbial strains isolated from the oral cavity of patients undergoing prolonged antibiotic therapy, including 12 Staphylococcus, 12 Enterobacteriaceae, and 12 Candida strains, were studied. The number of cells of each microorganism was standardized to 10(6) cells/mL. Twenty-four assays were carried out for each strain according to the following experimental conditions: gallium-aluminum-arsenide laser and photosensitizer (n = 6, L+P+), laser and physiologic solution (n = 6, L+P-), photosensitizer (n = 6, L-P+), and physiologic solution (n = 6, L-P-). Next, cultures were prepared on brain-heart infusion agar for the growth of Staphylococcus and Enterobacteriaceae, and on Sabouraud dextrose agar for the growth of Candida, and incubated for 48 h at 37 degrees C. The results are reported as the number of colony-forming units (CFU/mL) and were analyzed with analysis of variance and the Tukey test. Results: The Staphylococcus, enterobacterial, and Candida strains were sensitive to photodynamic therapy with malachite green (L+P+). A reduction of similar to 7 log(10) for Staphylococcus, 6 log(10) for enterobacteria, and 0.5 log(10) for the genus Candida. Significant statistical differences were observed between the L+P+ groups and the control groups (L-P-). Conclusion: The Staphylococcus, Enterobacteriaceae, and Candida strains studied were sensitive to photodynamic therapy with malachite green.